Peripheral blood methylation profiling of female Crohn's disease patients. Issue 1 (December 2016) - Li Yim, Andrew; Duijvis, Nicolette; Zhao, Jing; de Jonge, Wouter; D'Haens, Geert; Mannens, Marcel; Mul, Adri; te Velde, Anje; Henneman, Peter
Abstract Background Crohn's disease (CD) is a chronic inflammatory disorder belonging to the inflammatory bowel diseases (IBD). CD affects distinct parts of the gastrointestinal tract, leading to symptoms including diarrhea, fever, abdominal pain, weight loss, and anemia. The aim of this study was to assess whether the DNA methylome of peripheral blood cells can be associated with CD in women. Methods Samples were obtained from 18 female patients with histologically confirmed ileal or ileocolic CD and 25 healthy age- and gender-matched controls (mean age and standard deviation: 30.5 ± 6.5 years for both groups). Genome-wide DNA methylation was determined using the Illumina HumanMethylation 450k BeadChip. Results Our analysis implicated 4287 differentially methylated positions (DMPs; correctedp < 0.05) that are associated to 2715 unique genes. Gene ontology enrichment analysis revealed significant enrichment of our DMPs in immune response processes and inflammatory pathways. Of the 4287 DMPs, 32 DMPs were located on chromosome X with several hits for MIR223 and PABPC5. Comparison with previously performed (epi)genome-wide studies revealed that we replicated 33 IBD-associated genes. In addition to DMPs, we found eight differentially methylated regions (DMRs). Conclusions CD patients display a characteristic DNA methylation landscape, with the differentially methylated genes being implicated in immune response. Additionally, DMPs were found on chromosome X suggesting X-linked manifestations of CD that could be associated with female-specific symptoms.